The Effect of stem education on pre-service science teachers’ perception of ınterdisciplinary education - Çınar, Sinan; Pırasa, Nimet; Uzun, Neslihan; Erenler, Sümeyye (Journal of Turkish Science Education, 2016)
In both Turkey and the other countries, disciplines in curricula emphasize interdisciplinary approach under the heading of “related with the other courses”. STEM education is one of these approaches. One major problem faced by STEM education is the shortage of professional programs which guide teachers about the relationship between STEM disciplines and how to teach it in class. This study was carried out to investigate the change in pre-service science teachers’ perspective of interdisciplinary relation after giving them pre-service education on interdisciplinary STEM education. Case study research model was used in the study. The study was conducted with 32 pre-service science teachers in the third grade in Recep Tayyip Erdogan University, Faculty of Education during the fall semester in the 2015-2016 academic year. In the scope of this study, science pre-service teachers were given pre-service education on interdisciplinary STEM approach; pre-test and post-test data were collected by applying the STEM-WAT and STEM surveys to the participants; and the collected data were analyzed with descriptive analysis. According to the pre-test results, the participants were able to relate science education to various disciplines prior to the STEM education. In the post-test results, despite a decrease in the number of disciplines related to natural sciences, an evident increase was reported in the number of relations with certain disciplines such as Mathematics, Technology and Engineering. Before the STEM education, pre-service teachers were thinking of relating teaching Natural Sciences to just Mathematics in their future classes. After the STEM education, they were reported to think of relating their teaching with Mathematics, Technology and Engineering. Moreover almost all pre-service teachers think of benefiting from relation of natural sciences with other disciplines in their classes. They thought that such relation would be useful for both individual and social development of students and instruction.